Direct noninvasive 1 H NMR analysis of stream water DOM Insights into the effects of lyophilization compared with whole water - Whitty, Stephanie D (Magnetic resonance in chemistry : MRC, 2021)
© 2019 John Wiley & Sons, Ltd.